Soaring Towards Positive Change: Reflection on an Action Research Case in Double Loop Learning Process - Hsing Lu, Ph.D., Lee (ABAC ODI JOURNAL Vision. Action. Outcome, 2015)
Abstract This “SOARING Towards Positive Change: Reflection on an Action Research case study in Double Loop Learning Process” assesses the willingness of Thailand and Indonesia management to assimilate and apply Western-style OD - SOAR to help them manage the strategic planning and problem-solving in the context of their institutions. The following research questions were posed: Are Thailand and Indonesia managers willing to apply OD (SOAR)? From these managers perception, how would (OD) SOAR be adapted and implemented as managers’ theory-in-use? The author used Hofstede’s cultural dimension values survey and Likert profile organization characteristics survey to diagnose managers’ willingness to change during contextual shifts: (a) to describe the current organizational climate; (b) to discern how managers perceive an ideal organizational climate and the ideal culture from which it derives; and (c) to identify how SOAR can be applied within an organization and how it can improve strategic planning. The Likert profile of organization characteristics was selected for ease of use and appropriateness for Thailand and Indonesia culture. This study references institutional theory, SOAR Profile Pilot Survey, Hofstede’s cultural dimension values survey, and Double loop learning to illustrate how managers institutionalize strategic planning when facing the ambiguities of learning and applying Western management through SOAR processes to reach Double loop learning. effect. How the SOR motion is used Three groups of Ph. D. students (managers) were selected for this case study: One (Indonesia group) from the Academic sector, the other two (Thailand groups) from private firms in various industrial sectors. Survey results showed all groups have similar perceptions regarding current and future organizational characteristics, but individuals who received institutionalized, overseas training improved more during training in perceiving ideal future organizational characteristics. This study concludes that Thailand and Indonesia managers are willing to apply OD (SOAR) for change, but their perceptions can be changed more effectively through strategically institutionalized learning processes than by simple association. Through OD classes, all three groups are conducting Action research at target organization with SOAR strategic planning; process of these case studies could bring positive change through double loop learning. Keywords: SOAR, positive change, double loop learning